Sedimentary facies and depositional model of the Lower Cretaceous Quiricó Formation (Sanfranciscana Basin, Brazil) and their implication for the occurrence of vertebrate fauna at the Coração de Jesus region - Cabral, Victor Carvalho [UNESP]; Mescolotti, Patricia Colombo [UNESP]; Varejão, Filipe Giovanini (Elsevier, 2021)
The Coração de Jesus region, northern Minas Gerais state, Brazil, is highly relevant in the Sanfranciscana Basin context due to the presence of titanosaurs, abelisaurids, and noasaurids. However, there is a poor stratigraphic constrain of the occurrences and few paleoenvironmental investigations in the area. Herein, a detailed sedimentologic and stratigraphic investigation of the fossiliferous succession is conducted to position the vertebrate assemblage in the stratigraphy. The sedimentary rocks are interpreted as part of the Quiricó Formation (Areado Group), representing the thickest occurrence of the unit (ca. 56 m) to the north of the Abaeté sub-basin. There, two main sedimentary successions are recognized, with the lower succession dominated by mudstone facies, and the upper succession dominated by sandstone facies. Vertebrate fossils and trace fossils of the species Taenidium barretti, Skolithos isp. and Arenicolites isp. are recorded uniquely within the lower succession, where wetter environmental conditions prevailed. The sedimentary succession is interpreted as a lacustrine system with increasing influence of eolian processes, which suggests an intensification of the aridity in the region during Lower Cretaceous.
Keywords: Areado group; Lacustrine system; Quiricó formation; Trace fossils